2008
DOI: 10.1210/jc.2008-0842
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Autoimmune Hyperthyroidism Relapse in Children after Discontinuation of Antithyroid Drug Treatment

Abstract: A longer initial duration of euthyroid state with ATD seems to be the only variable related to the risk of hyperthyroidism relapse in children that can be manipulated. Ethnic origin, age, and severity of the disease at diagnosis may guide long-term disease management decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
159
2
18

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(187 citation statements)
references
References 43 publications
8
159
2
18
Order By: Relevance
“…There is some controversy on the use of MMI as a first-line treatment of pediatric hyperthyroidism and we used, similar to other studies, methimazole as the first-line therapy in all patients [19,20,[22][23][24][25]. Remission rates after ATD withdrawal varied in different studies ranging from 33% to 64% [6,23,26].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…There is some controversy on the use of MMI as a first-line treatment of pediatric hyperthyroidism and we used, similar to other studies, methimazole as the first-line therapy in all patients [19,20,[22][23][24][25]. Remission rates after ATD withdrawal varied in different studies ranging from 33% to 64% [6,23,26].…”
Section: Discussionmentioning
confidence: 90%
“…Many retrospective studies [19,25,31,32] and one prospective study have shown that the duration of medical treatment may be a predictive marker of relapse in juvenile hyperthyroidism. Another prospective study showed that relapse risk of hyperthyroidism decreased with the duration of the first course of ATD and every additional year of ATD therapy was associated with a decrease in the relapse rate [20]. Another study evaluated the effect of the duration of ATD treatment after three consecutive courses, each lasting for 2 years and found a remission rate of 50% after discontinuation of ATD treatment [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is difficult to achieve long-term compliance and the rate of relapse is high in children. Remission is achieved in less than 30% of children after a first course of ATD for about 2 years (18). In children, studies have shown that a longer initial duration of euthyroid state with ATD is associated with a lower risk of relapse after a first course of ATD therapy (18,19).…”
Section: No1 February 2013mentioning
confidence: 99%